PERLAKUAN AKUNTANSI PENDAPATAN DAN BEBAN BERBASIS SAK ETAP DAN IMPLIKASINYA PADA LAPORAN KEUANGAN KOPERASI KARYAWAN KARYA SAMPURNA PT. BANK MANDIRI - Salindeho, Anggelina Chrisdayanti; Kalangi, Lintje; Pangerapan, Sonny (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Cooperative is an association established by persons or legal entities of cooperatives that have limited economic ability, with the aim to improve the welfare of its members. Revenues and expenses are an important component of financial statements because different treatment of income and expenses will result in changes in the resulting financial statements. Financial Accounting Standards intended for cooperative entities are SAK ETAP. This study aims to determine the accounting treatment of income and expenses on Cooperative Employees Karya Sampurna PT. Bank Mandiri in accordance with SAK ETAP. The research method used in this thesis research is descriptive method whose purpose each data collected in the analysis and then drawn a conclusion and the type of research used is qualitative descriptive. The results obtained that the accounting treatment of income and expenses on Cooperative Employees Karya Sampurna PT. Bank Mandiri is in compliance with SAK ETAP.Keywords: Accounting treatment, income, expenses.